Prevalence and Associated Factors of Sexual Dysfunction in Patients With Inflammatory Bowel Disease - Zhang, Jinzhi; Nie, Jiao; Zou, Min; Zeng, Qishan; Feng, Yue; Luo, Zhenyi; Gan, Huatian (Frontiers in Endocrinology, 2022)
Background Sexual dysfunction (SD) in patients who suffer from inflammatory bowel disease (IBD) has not attracted widespread attention, and thus research studies are scarce. Objective This study aims to evaluate the rates of SD in IBD compared with healthy individuals and elucidate the associated factors. Methods In this cross-sectional study, the Female Sexual Function Index (FSFI) and the simplified version of the International Index of Erectile Function (IIEF-5) were filled by IBD patients, as well as healthy control individuals. Results A total of 208 IBD patients, including 133 with Crohn’s disease (CD) and 75 with ulcerative colitis (UC), and 190 healthy individuals filled out the questionnaires. In women, SD rates were 61.9% in the patients with IBD vs. 24.4% in the healthy controls (p < 0.01). In men, the rates of erectile dysfunction (ED) were 43.5% in the patients with IBD vs. 12.5% in the healthy controls (p < 0.01). Anxiety (OR, 3.092; 95%CI: 1.033-9.252, p = 0.044) and active perianal disease (OR, 4.481; 95%CI: 1.055-19.029, p = 0.042) were independent risk factors for SD in female IBD patients. age (OR, 1.050; 95%CI: 1.007-1.095, p = 0.022), depression (OR, 5.763; 95%CI: 1.864-17.821, p = 0.002) and active perianal disease (OR, 7.117; 95%CI: 1.747-28.983, p = 0.006) were independent risk factors for ED in male patients. Conclusions In the IBD patients, 62% of women reported having SD, and 44% of men reported having ED. These higher rates, as compared to the healthy controls, are mostly driven by active perianal disease and psychological factors.